2016
DOI: 10.1101/gad.290312.116
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of distant chromosomal loci in space in E. coli: a bacterial nucleolus

Abstract: The spatial organization of DNA within the bacterial nucleoid remains unclear. To investigate chromosome organization in Escherichia coli, we examined the relative positions of the ribosomal RNA (rRNA) operons in space. The seven rRNA operons are nearly identical and separated from each other by as much as 180°on the circular genetic map, a distance of ≥2 million base pairs. By inserting binding sites for fluorescent proteins adjacent to the rRNA operons and then examining their positions pairwise in live cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 52 publications
(76 reference statements)
10
57
1
Order By: Relevance
“…RNAP is distributed throughout the nucleoid in cells grown in minimal media, but concentrates into distinct clusters in cells grown in rich media (31,32). This nutrient-dependent localization has been well-characterized (33,34), but the mechanism(s) that govern RNAP clustering remains unclear (35,36). Here, we show that clusters of bacterial RNAP are biomolecular condensates.…”
Section: Introductionmentioning
confidence: 66%
“…RNAP is distributed throughout the nucleoid in cells grown in minimal media, but concentrates into distinct clusters in cells grown in rich media (31,32). This nutrient-dependent localization has been well-characterized (33,34), but the mechanism(s) that govern RNAP clustering remains unclear (35,36). Here, we show that clusters of bacterial RNAP are biomolecular condensates.…”
Section: Introductionmentioning
confidence: 66%
“…One possible explanation derives from the very different spatial distributions of actively transcribing RNA polymerase copies in the two conditions. In fast growth, most transcription occurs on the seven rrn operons, six of which have been shown to cluster with each other (Gaal et al, 2016). These 'transcription foci' (Jin et al, 2013) tend to locate at the periphery of the nucleoid (Jin et al, 2013;Stracy et al, 2015), perhaps due to excluded volume effects (Mondal et al, 2011).…”
Section: Degree Of Nucleoid Compaction In Fast and Slow Growthmentioning
confidence: 99%
“…Taken together, these results argued strongly against the hypothesis that rRNA transcription activity from multiple rrn operons contributes significantly to the spatial organization of RNAP. Consistent with this notion, a recent study reported that multiple rrn operons could colocalize with each other independent of rRNA transcription activity 34 .…”
Section: Discussionmentioning
confidence: 63%
“…Next, we reasoned that while rRNA transcription activity was diminished in cells treated with rifampicin or serine hydroxamate, it is possible that RNAP remained associated with multiple rrn operons that spatially colocalize with each other 34 , despite the lack of high transcription activity from these operons. To examine this possibility, we used a Δ 6rrn strain, in which six out of seven rrn operons (except for rrnC) were removed from the chromosome 16 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation